The Effect of Fintech Payment on Household Consumption Expenditure (Study Case in West Java) - Nursafarina, Aulia; Firmialy, Sita Deliyana (SEIKO : Journal of Management & Business, 2023)
This article examines the impact of fintech payments on the consumption expenditures of West Java households. Quantitative methods were used in this study. Survey information in the form of a questionnaire was distributed to 111 households in West Java utilizing a fintech payment application. This study employs both descriptive and regression analysis. This study discovered that the personal mobility (PM) fintech payment variable has a positive and statistically significant influence on the household consumption expenditure variable, total cost accommodation (TCA), total cost transportation (TCC), and total cost communication (TCC) (TCCI). In addition, the fintech payment variable, ease of use, has a positive and statistically significant effect on the household consumption expenditure variable, total cost other cost (TCOC). Moreover, the occupation control variable has a positive and statistically significant effect on total cost (TC), total cost of food and beverage (TCF), and total cost of lodging (TCL) (TCA). The control variable sex has a positive and significant effect on total cost education (TCED), while the control variable marital status has a positive and significant effect on total cost (TC), total cost household goods (TCHG), and total cost transportation (TCTC) (TCED). This study examines the relationship between fintech payments and household consumption expenditures. This study is anticipated to serve as a resource for future researchers. Keywords: fintech payment, household consumption expenditure